KUALITAS PELAYANAN DAN LOYALITAS PENGGUNAAN OJEK SEPEDAMOTOR SEBAGAI ANGKUTAN UMUM PENUMPANG PERKOTAAN - Bahar, Taslim (MEKTEK, 2013)
Limited access to Public Transport (PT) to serve the needs of PT urban population will lead to theÂ emergence of alternative PT. Limited access PT is partly due to the limited size of the geometric road and thelimited range of PT services. This generally occurs in the cities of Indonesia and one of its effects is theemergence of alternative public transport passengers is ojek motorcycles. Ojek Motorcycle(MC) appears dueto user response to the needs of PT and tends to consumer increases in Indonesian cities. How the user'sperception of the ojek MC service and whether the ojek MC still needed as part of the urban public transportpassenger? This study aims to investigate the factors that affect the quality of service and loyalty to the ofMC ojek transport as Â urban passenger public transport. Survey has been done in Bandung city and datacollection by questionnaires and interviews directly to the user. The analysis was done with the approach ofthe causal relationship between the factors that influence with method of structural equation modeling(SEM).The study shows that the convenience factor/flexibility, time, Accessibility, safety and driver attitudes providea strong reflection to service quality of ojek MC. Factors pollution caused by the operation of ojek MC doesnot reflect the quality of service. While the indicators: it would continue the use of modes and wouldrecommend the use of other modes to give a good reflection of the loyalty. Quality of service has a stronginfluence on satisfaction, furthermore, satisfaction strong influence on the use of ojek MC loyalty.Keywords: Ojek Motorcycle, SEM, loyalty, service, quality